Frequency of Retinopathy of Prematurity in Infants Born Before 34 Weeks of Gestation - Zaheer Ud Din Aqil Qazi; Dua Zahid; Baby Nisha; Farhat Khan (Indus Journal of Bioscience Research, 2025)
Background: Retinopathy of prematurity (ROP) is a proliferative retinal disorder that primarily affects preterm infants with incomplete retinal vascularization. Objective: To determine the frequency of ROP in infants born before 34 weeks of gestation and identify associated risk factors. Methods: This Cross-sectional study was conducted at the Hameed Latif Hospital, Lahore from 1st Oct 24 to 31st March 2025. Data were collected through non-probability consecutive sampling. The calculated sample size was 124 neonates. For each enrolled participant, demographic and clinical data including gestational age, gender, birth weight, days since admission, and supplemental oxygen therapy status (given/not given and duration in days) were recorded by the researcher on a predesigned proforma. Results: Out of 124 infants, 19 (15.3%) were diagnosed with ROP. A significant association was found between ROP and gestational age